2018
DOI: 10.1016/j.jad.2017.11.050
|View full text |Cite
|
Sign up to set email alerts
|

Parental bonding and adolescents’ depressive and anxious symptoms in Pakistan

Abstract: Findings of this study indicate that parental bonding is a central construct within a developmental framework in the cultural context of Pakistan, and is important when considering long-term psychosocial functioning of individuals. It should be explored further in clinical populations of Pakistani adolescents to ascertain significance of these constructs for interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 54 publications
2
16
1
Order By: Relevance
“…Levels of lack of autonomy were elevated in all three affected groups compared with the unaffected persons. Generally, our findings contradict most of earlier findings that perceived authoritarian parenting is not related to adult depression and anxiety (e.g., Enns et al, 2002;Khalid et al, 2018). While some studies found that reported lack of autonomy have been shown to relate to increased adult psychopathology risk (Kendler et al, 2000;Seganfredo et al, 2009), others showed that, when controlling for the effects of care, associations between lack of autonomy and affective disorders were reduced (Gerlsma, Emmelkamp, & Arrindell, 1990) or no longer significant (Kendler et al, 2000;Khalid et al, 2018).…”
Section: Table 3 Comparison Of Psychopathology Groups On Clinical and Demographic Characteristicscontrasting
confidence: 99%
See 1 more Smart Citation
“…Levels of lack of autonomy were elevated in all three affected groups compared with the unaffected persons. Generally, our findings contradict most of earlier findings that perceived authoritarian parenting is not related to adult depression and anxiety (e.g., Enns et al, 2002;Khalid et al, 2018). While some studies found that reported lack of autonomy have been shown to relate to increased adult psychopathology risk (Kendler et al, 2000;Seganfredo et al, 2009), others showed that, when controlling for the effects of care, associations between lack of autonomy and affective disorders were reduced (Gerlsma, Emmelkamp, & Arrindell, 1990) or no longer significant (Kendler et al, 2000;Khalid et al, 2018).…”
Section: Table 3 Comparison Of Psychopathology Groups On Clinical and Demographic Characteristicscontrasting
confidence: 99%
“…. let me dress in any way I pleased" is referred to as "authoritarianism" (Enns et al, 2002;Heider et al, 2005;Kendler et al, 1996Kendler et al, , 2000Khalid, Qadir, Chan, & Schwannauer, 2018). Items of the authoritarianism subscale are generally reverse coded to ensure that high values reflect authoritarian parenting.…”
Section: Factor Structure Of the Pbimentioning
confidence: 99%
“…These results demonstrate that both emotion‐focused coping and secondary attachment insecurity contribute to adolescent psychological distress. One explanation for this finding could be that attachment with parents (primary attachment) is likely to be more obedience‐oriented while with siblings or friends (secondary attachment) more emotionally close relationship is expected within a Pakistani context (Khalid, Qadir, Chan, & Schwannauer, 2017). This suggests that targeting adolescent secondary attachment security could reduce the influence of emotion‐focused coping on psychological distress.…”
Section: Discussionmentioning
confidence: 99%
“…However, most existing data comes from western cultures where individualistic themes predominate. While some studies highlight differences between the two (Wang and Leichtman, 2000), evidence from eastern collectivist cultures, including Pakistan, is scarce (Masud et al, 2015; Khalid et al, 2018).…”
Section: Introductionmentioning
confidence: 99%